A hydrogenation catalyst and its preparation method and application
By using hydrogenation catalysts with components such as HZSM-23@Al-SBA-15 composite molecular sieve and modified Y molecular sieve, the problems of poor diesel freezing point reduction and insufficient catalyst stability in the prior art are solved, and the effect of efficiently reducing diesel freezing point and improving diesel quality is achieved.
Patent Information
- Application Number
- CN202210777976.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-07-04
- Publication Date
- 2025-04-01
- Estimated Expiration
- 2042-07-04
AI Technical Summary
Existing hydrogenation catalysts are not effective in reducing diesel freezing points, especially when treating macromolecular raw oils, the stability and acid suitability of the catalyst are insufficient.
The HZSM-23@Al-SBA-15 composite molecular sieve was used as the core component to improve its crystallinity and pore structure through water vapor hydrothermal treatment, combined with modified Y molecular sieve and alumina, and added Group VIB and Group VIII active metals to form a new hydrogenation catalyst.
This catalyst not only ensures diesel yield while significantly reducing diesel freezing point, but also improves the conversion capacity of macromolecular raw materials and enhances the stability and acid suitability of the catalyst.
Smart Images

Figure CN117380262B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a hydrogenation catalyst and a preparation method and application thereof, and in particular to a hydrogenation catalyst that can be used to reduce the freezing point of diesel and a preparation method and application thereof. Background Art
[0002] The hydroisomerization and degassing technology requires the use of a bifunctional catalyst. The active metal is dispersed on the surface of the molecular sieve with acid function to play the hydrogenation and dehydrogenation function, while the molecular sieve uses its pore characteristics and acid properties to implement shape-selective catalysis on the molecular chain of the oil product to achieve skeletal isomerization.
[0003] CN1762594A discloses an alkane hydroisomerization catalyst. The catalyst is prepared by compounding a variety of ten-membered ring one-dimensional pore molecular sieves such as ZSM-22, ZSM-23, SAPO-11, and EU-1. Since the molecular sieves have low weak acid and medium-strong acid content, which causes long-chain alkane chain scission, the base oil yield is low when the reaction temperature is 325°C.
[0004] CN108816279A discloses an isomerization dewaxing catalyst. It uses a series of ten-membered ring molecular sieves such as ZSM-22, ZSM-23, SAPO-11, EU-1, ZSM-48, NU-10 as carriers, and loads precious metals to prepare a normal alkane isomerization dewaxing catalyst. Similarly, due to the low content of weak acid and medium-strong acid in the molecular sieve, the selectivity and yield of the catalyst for base oil at 318 ° C are still low.
[0005] In addition, as oil products gradually become heavier and inferior, the ability of catalysts to process macromolecular crude oil also needs to be improved. In the preparation method of the pour point catalyst disclosed in patent CN111659462A, the primary chain breaking ability of macromolecular linear alkanes is enhanced by acid washing the strong acid molecular sieve β, and at the same time, the ten-membered ring molecular sieve ZSM-22 is added to the catalyst for hydrogenation isomerization, and the two synergistically promote the conversion of heavy oil molecules. However, the acid washing step easily destroys the structure of the β molecular sieve, affecting the stability of the catalyst.
[0006] Therefore, developing a hydrogenation catalyst with strong conversion ability for macromolecular raw materials and suitable acidity to improve the low-temperature fluidity of oil products is of great significance to solving the problem of improving oil performance. Summary of the invention
[0007] In order to overcome the deficiencies in the prior art, the present invention provides a hydrogenation catalyst and a preparation method and application thereof. The catalyst has stable properties and can significantly reduce the diesel pour point while ensuring the diesel yield.
[0008] The first aspect of the present invention provides a hydrogenation catalyst, which comprises the following components based on the weight of the final catalyst:
[0009] a) HZSM-23@Al-SBA-15 composite molecular sieve, with a content of 10-50wt%, preferably 15-45wt%;
[0010] b) modified Y molecular sieve, the content is 2-8wt%, preferably 3-6wt%;
[0011] c) aluminum oxide, with a content of 25-65wt%, preferably 30-60wt%;
[0012] d) Group VIB and / or Group VIII active metals, wherein the content of Group VIB metals as oxides is 10-30 wt%, and the content of Group VIII metals as oxides is 3-10 wt%;
[0013] The HZSM-23@Al-SBA-15 composite molecular sieve has the HZSM-23 molecular sieve as the core and the Al-SBA-15 molecular sieve as the shell, wherein the crystallinity of the core molecular sieve is 95-110%, preferably 97-108%.
[0014] In the catalyst of the present invention, after the composite molecular sieve is hydrothermally treated with 600° C. steam for 2 hours, the crystallinity of the core molecular sieve is 95-108%, preferably 96-105%.
[0015] In the catalyst of the present invention, the total acid amount of the catalyst is 0.100-0.285 mmol / g, and the weak acid content is 50-85%; preferably, the total acid amount is 0.110-0.280 mmol / g, and the weak acid content is 53-82%.
[0016] In the catalyst of the present invention, the mesopore volume of the catalyst accounts for 15-60% of the total pore volume, preferably 18-55%.
[0017] In the catalyst of the present invention, the specific surface area of the catalyst is 250-400 m 2 / g, pore volume is 0.50~0.85 cm 3 / g; preferably 260~385 m 2 / g, and the pore volume is preferably 0.53~0.80 cm 3 / g.
[0018] A second aspect of the present invention provides a method for preparing a hydrogenation catalyst, the method comprising the following steps:
[0019] (1) Preparation of HZSM-23@Al-SBA-15 composite molecular sieve;
[0020] (2) mixing the HZSM-23@Al-SBA-15 prepared in step (1), the modified Y molecular sieve, alumina and a binder, forming, drying and calcining to obtain a carrier;
[0021] (3) Introducing active metal components into the carrier obtained in step (2), and obtaining the final catalyst after drying and calcining.
[0022] In the method of the present invention, the HZSM-23@Al-SBA-15 composite molecular sieve in step (1) has HZSM-23 molecular sieve as the core and Al-SBA-15 molecular sieve as the shell, wherein the crystallinity of the core molecular sieve is 95-110%, preferably 97-108%; after the composite molecular sieve is hydrothermally treated with water vapor at 600°C for 2 hours, the crystallinity of the core molecular sieve is 95-108%, preferably 96-105%.
[0023] In the method of the present invention, the total acid content of the HZSM-23@Al-SBA-15 composite molecular sieve in step (1) is 0.07~0.35 mmol / g, preferably 0.09~0.32 mmol / g; the weak acid content is 60~95%, preferably 65~92%; the mass content of Al in the Al-SBA-15 molecular sieve calculated as alumina is 2.45~10.05%, preferably 2.83~8.50%, based on the weight of the Al-SBA-15 molecular sieve; the core-shell mass ratio in the composite molecular sieve is 1:1~1:9, preferably 1:2~1:4.
[0024] In the method of the present invention, the micropore volume of the HZSM-23@Al-SBA-15 composite molecular sieve in step (1) accounts for 15-90% of the total pore volume, preferably 20-85%; the specific surface area is 310-470 m 2 / g, pore volume is 0.31~0.68 cm 3 / g, preferably, the specific surface area of the composite molecular sieve is 330-460 m 2 / g, pore volume is 0.32~0.65 cm 3 / g.
[0025] In the method of the present invention, the modified Y molecular sieve SiO 2 / Al 2 O 3 The molar ratio is 25-90, the unit cell parameters are 2.460-2.470, and the specific surface area is 550-850 m 2 / g, pore volume is 0.35~0.53 cm 3 / g.
[0026] In the method of the present invention, the properties of the alumina in step (2) are: a specific surface area of 375-400 m2 / g, pore volume 0.60~0.95 cm 3 / g.
[0027] In the method of the present invention, the carrier in step (2) is dried and calcined by conventional methods, specifically as follows: the drying temperature is 80-120°C and the time is 2-12 hours; the calcination temperature is 530-570°C and the time is 3-6 hours.
[0028] In the method of the present invention, the active metal component in step (3) is one or a combination of two of Mo, W, Ni, Fe, and Co, preferably a combination of W-Ni and Mo-Ni.
[0029] In the method of the present invention, the active metal loading method in step (3) can adopt a conventional loading method in the prior art, preferably an impregnation method. After impregnation, the carrier is dried at 80-120°C for 4-7 hours, and then calcined at 400-700°C for 3-12 hours to obtain the final catalyst.
[0030] The above catalyst is suitable for the reaction of reducing the condensation point of a diesel fraction with a high content of paraffins and cycloalkanes, wherein the total mass content of paraffins and cycloalkanes in the diesel is 61-85%, the mass content of paraffins is 32-50%, and the mass content of cycloalkanes is 20-40%; preferably, the total mass content of paraffins and cycloalkanes is 62-83%, the mass content of paraffins is 34-47%, and the mass content of cycloalkanes is 22-38%.
[0031] In the above application, the density of diesel is 0.870~0.930 g / cm 3 , preferably 0.880~0.925 g / cm 3 ; Distillation range is 150~390 ℃.
[0032] In the above application, the reaction conditions are as follows: reaction temperature 320~400 ℃, total reaction pressure 4.0~12.0 MPa, liquid hourly volume space velocity 0.4~2.0 h -1 , hydrogen-oil volume ratio 400:1~1200:1.
[0033] In the preparation method of the HZSM-23@Al-SBA-15 composite molecular sieve of the present invention, a microporous HZSM-23 molecular sieve with a high weak acid content is used as a core, and a mesoporous material Al-SBA-15 with controllable acid amount and acid strength is used as a shell. The prepared HZSM-23@Al-SBA-15 composite molecular sieve has a high weak acid content and a pore structure with a stepped size distribution, high stability, and controllable relative content of micro-mesopore pore volume, thereby improving the conversion ability of the microporous ZSM-23 molecular sieve to macromolecular substances in the raw material and also improving the stability of the mesoporous material SBA-15 during the application process.
[0034] When the catalyst of the present invention is used in the process of decondensation of inferior diesel, a small amount of modified Y molecular sieve partially opens the ring of macromolecular cycloalkanes or a small amount of polycyclic aromatic hydrocarbons in the oil product, and the generated macromolecular intermediates are further reacted through the acidic sites of the core-shell molecular sieve HZSM-23@Al-SBA-15 shell mesoporous material, but due to its weak acidity, the integrity of long-chain alkanes can be maintained, and the core molecular sieve ZSM-23 molecular sieve is contacted through the mesoporous pores. The rich weak acid sites can promote the occurrence of hydrogenation isomerization reactions of chain alkane molecules, improve isomerization selectivity, avoid hydrogenation cracking of straight-chain alkanes and excessive cracking of product molecules, reduce the diesel condensation point while ensuring the diesel yield, and greatly improve the diesel quality. In the method of the present invention, the core-shell molecular sieve HZSM-23@Al-SBA-15 core has a high degree of crystallinity, which significantly improves the stability of the catalyst. BRIEF DESCRIPTION OF THE DRAWINGS
[0035] Figure 1 This is the wide-angle XRD spectrum of the HZSM-23@Al-SBA-15 composite molecular sieve synthesized in Example 1 of the present invention, that is, the XRD spectrum of the core HZSM-23 molecular sieve.
[0036] Figure 2 This is the small-angle XRD spectrum of the HZSM-23@Al-SBA-15 composite molecular sieve synthesized in Example 1 of the present invention, that is, the XRD spectrum of the shell Al-SBA-15 molecular sieve. DETAILED DESCRIPTION
[0037] In order to better illustrate the present invention, the present invention is further illustrated below in conjunction with examples and comparative examples. However, the scope of the present invention is not limited to the scope of these examples.
[0038] In the preparation method of the catalyst of the present invention, the preparation method of the HZSM-23@Al-SBA-15 composite molecular sieve is as follows:
[0039] Preparation of core molecular sieve HZSM-23 molecular sieve:
[0040] ① preparing a mixed solution A containing a first template, and amorphous silicon aluminum and / or an amorphous silicon aluminum precursor;
[0041] ② Adding an alkali source and a silicon source to the mixed solution of step ①;
[0042] ③ The material obtained in step ② is crystallized, washed, dried, calcined, and ammonium exchanged to obtain HZSM-23 molecular sieve;
[0043] Preparation of HZSM-23@Al-SBA-15 composite molecular sieve
[0044] ① Add the silicon source into the acid solution and stir for a period of time, then let it stand and age to obtain the silicon source hydrolyzate;
[0045] ② The hydrolyzate obtained in (2) ①, the HZSM-23 molecular sieve obtained in (1) ③, the second template agent, and aluminum isopropoxide are uniformly mixed to obtain a mixed slurry B, which is then crystallized, washed, dried, and calcined to obtain a ZSM-23@SBA-15 composite molecular sieve.
[0046] In step (1) ① of the above method, the first template agent is one or more of isopropylamine, pyrrolidine, N,N-dimethylformamide, and dimethylamine.
[0047] In step (1) ① of the above method, the molar ratio of silicon (calculated as silicon oxide): aluminum (calculated as aluminum oxide) in the mixed solution A is 1:(0.10~0.85), preferably 1:(0.20~0.79), and more preferably 1:(0.24~0.78); the molar ratio of aluminum (calculated as aluminum oxide): template is 1:(10~100), preferably 1:(15~85), and more preferably 1:(20~65).
[0048] In step (1) ① of the above method, an amorphous silicon-aluminum precursor is prepared by a carbonization method, and then a first template is added to the amorphous silicon-aluminum precursor to obtain the mixed solution.
[0049] A non-limiting amorphous silicon-aluminum precursor preparation process in the embodiment of the present invention is as follows: prepare an aluminum source solution (preferably sodium aluminate) and a silicon-containing compound solution respectively; mix the aluminum source solution with part of the silicon-containing compound solution, and introduce CO 2 Gas gelation occurs when CO is introduced 2 When the gas volume accounts for 50-100% of the total volume introduced, preferably 70-90%, the remaining silicon-containing compound solution is added, and the remaining CO is introduced. 2 The gas is optionally aged to obtain an amorphous silicon-aluminum precursor.
[0050] In the above-mentioned process of preparing the amorphous silicon-aluminum precursor, the remaining part of the silicon-containing compound solution, calculated as silicon dioxide, accounts for 5-85 wt %, preferably 30-70 wt %, of the total amount of the silicon-containing compound solution added, calculated as silicon dioxide.
[0051] In the above-mentioned preparation process of the amorphous silicon-aluminum precursor, the reaction temperature of the gelling is 10-40°C, preferably 15-35°C, and the pH value after the gelling is controlled to be 9-12.
[0052] In the above-mentioned process of preparing the amorphous silicon-aluminum precursor, the silicon-containing compound solution is water glass and / or sodium silicate solution.
[0053] In the above-mentioned amorphous silicon aluminum precursor preparation process, A1 2 O 3The concentration of the aluminum source solution is 15-60 gAl 2 O 3 / L, SiO 2 The concentration of the silicon-containing compound solution is 40-260 gSiO 2 / L, the CO 2 The concentration of the gas is 30~60 v%.
[0054] In the above-mentioned preparation process of the amorphous silicon aluminum precursor, the aging time is 5 to 60 minutes, and the aging temperature is 10-40°C.
[0055] In step (1) ① of the above method, the mixed solution A is stirred at 10-35° C. for 0.2-2 hours.
[0056] In step (1) ② of the above method, the aluminum (calculated as aluminum oxide) in the mixed solution A of step (1) ① is used as the reference, and the SiO 2 :Al 2 O 3 :R 2 O (alkali source, where R is an alkali metal, such as sodium or potassium): H 2 O=1:(0.0025-0.025): (0.015-0.08):(30-80), template (SDA) / SiO 2 = 0.10 ~ 1.8 total feed molar ratio, preferably SiO 2 / Al 2 O 3 50~200, H 2 O / SiO 2 30~60, R 2 O / SiO 2 is 0.025~0.06, and an alkali source and a supplementary silicon source are added to the material in step (1)①.
[0057] In step (1)② of the above method, the silicon source is one or more of fumed silica, silica sol and water glass, and the alkali source is one or more of sodium hydroxide, potassium hydroxide and ammonia water.
[0058] In step (1) ③ of the above method, the crystallization conditions are: crystallization at 150-200°C for 8-72 hours; drying temperature is 80-120°C for 4-8 hours; calcination temperature is 530-570°C for 3-6 hours.
[0059] In step (1) ③ of the above method, the ammonium exchange is carried out by a conventional method, such as one or more ammonium exchanges, and the Na in the ZSM-23 molecular sieve after the ammonium exchange is 2The O content is less than 0.2%; it can then be washed, dried and calcined, wherein the drying temperature is 80~120 ℃ and the time is 4~8 hours; the calcination temperature is 530~570 ℃ and the time is 3~6 hours.
[0060] In step (2) ① of the above method, the silicon source is one or both of ethyl orthosilicate and methyl orthosilicate. The acid is one or more of hydrochloric acid, nitric acid and sulfuric acid. The pH of the acid solution is 1.0-4.0.
[0061] In step (2) ① of the above method, the stirring time is 4 to 10 hours, the temperature is 20 to 45°C, and the standing aging time is 8 to 48 hours.
[0062] In step (2) ② of the above method, the second template is a polyethylene oxide-polypropylene oxide-polyethylene oxide triblock copolymer (P123); preferably, aluminum isopropoxide and template P123 are first dissolved in an acid solution, respectively, and then mixed with other raw materials. The acid is one or more of hydrochloric acid, nitric acid, and sulfuric acid. The molar concentration of hydrogen ions in the acid solution is 0.1-0.7 mol / L, preferably 0.2-0.6 mol / L.
[0063] In step (2) ② of the above method, the mass ratio of P123 to HZSM-23 is 0.15-0.55, preferably 0.18-0.50; the mass ratio of the added silicon source to HZSM-23 is 1-4, preferably 1.2-3; the mass ratio of the added deionized water to HZSM-23 is 18-50, preferably 20-40; the SiO in the silicon source is 2 With Al in aluminum isopropoxide 2 O 3 The molar ratio is 15-120, preferably 20-100.
[0064] In step (2) ② of the above method, the mixed solution B needs to be stirred continuously at 15-30° C. for 6-8 hours before crystallization.
[0065] In step (2)② of the above method, the crystallization temperature of the mixed solution B is 80-120°C, and the crystallization time is 16-40 hours.
[0066] In step (2) ② of the above method, the drying temperature is 80-120 ºC and the time is 4-8 hours; the roasting temperature is 530-570 ºC and the time is 3-6 hours.
[0067] In the present invention, the relative crystallinity is measured by XRD, and the crystallinity of the core molecular sieve HZSM-23 prepared in step (1) of Example 1 is taken as a benchmark, which is 100%, and the relative crystallinity of other samples is obtained by comparison with it.
[0068] The specific surface area and pore volume were measured by low-temperature liquid nitrogen physical adsorption method using ASAP 2405 physical adsorption instrument produced by Micromeritics Corporation of the United States.
[0069] Total acid and weak acid content are determined by NH 3 Programmed temperature desorption (NH 3 -TPD), where the total acid content is the acid content corresponding to the desorption temperature of 120~500℃, and the acid content corresponding to the desorption temperature below 350℃ is the weak acid content.
[0070] Example 1
[0071] (1) Preparation of composite molecular sieves
[0072] ① The concentration is 40 gAl 2 O 3 / L sodium aluminate working solution, take the SiO 2 28 wt% sodium silicate solution, and then diluted to a concentration of 100 gSiO 2 / L sodium silicate working solution. Take 150 mL of sodium aluminate working solution and place it in a gelling tank, then add 50 mL of sodium silicate working solution, control the reaction temperature at 20 ºC, and introduce 50 v% CO 2 When the pH value reaches 10.0, stop the CO 2 , add 90 mL of sodium silicate working solution, and then pass the remaining CO 2 The gas was stable and after aging at 25 °C for 30 minutes, an amorphous silicon aluminum precursor was obtained. 2 :Al 2 O 3 :Na 2 O:H 2 O=1:0.02:0.04:45, IPA / SiO 2=0.7 total feed molar ratio (IPA is template agent isopropylamine), add isopropylamine to the amorphous silicon-alumina precursor obtained above, stir at 15 ℃ for 0.8 hours to obtain a mixed solution containing amorphous silicon-alumina precursor and template agent; then, add a mixture consisting of sodium hydroxide, silica sol and water to it, stir evenly to obtain silicon-alumina gel. The gel obtained above is poured into a stainless steel reactor and statically crystallized at 160 ℃ for 20 hours. After the crystallization is completed, it is filtered and washed to neutrality, and then dried at 120 ℃ to obtain the molecular sieve product NaZSM-23-1. Weigh a certain amount of NaZSM-23-1 molecular sieve sample, place it in an ammonium nitrate solution with a concentration of 2 mol / L, and the liquid-to-solid ratio is 10. After continuous stirring for 1 hour in a water bath at 80~90 ℃, filter and wash. After repeating the above operation process twice, the sample was placed in an oven at 80-100 °C for 8 hours and calcined in an air atmosphere at 550 °C for 3 hours to obtain HZSM-23-1.
[0073] ② Preparation of HZSM-23@Al-SBA-15 composite molecular sieve
[0074] a) 15.0 g of tetraethyl orthosilicate was added to 50.0 g of HCl solution with a pH value of 2.0, and the mixture was stirred at 40°C for 4 hours and allowed to stand for 36 hours to obtain a silicon source hydrolyzate.
[0075] b) 3.0 g P123 was dissolved in 250 mL 0.30 mol / L hydrochloric acid solution; 2.55 g aluminum isopropoxide, 10 g HZSM-23-1, and the silicon source hydrolyzate obtained in step ② a) were added successively, and stirred at room temperature for 4 hours; the resulting mixed solution was transferred to a hydrothermal reactor, crystallized at 100°C for 24 hours, filtered, washed to neutrality, dried at 100°C, and calcined in air at 550°C for 3 hours to obtain the molecular sieve product Z-1, and the relative crystallinity of the core molecular sieve was measured; after hydrothermal treatment with water vapor at 600°C for 2 hours, its hydrothermal stability was measured, and its XRD spectrum was as shown in the figure. Figure 1 and Figure 2 The specific properties are shown in Table 1.
[0076] Catalyst preparation
[0077] Alumina (surface area 387 m 2 / g, pore volume 0.82 cm 3 / g), 20 wt% Z-1 molecular sieve, 5 wt% modified Y molecular sieve (SiO 2 / Al 2 O 3 The molar ratio is 40, the unit cell parameter is 2.466, and the specific surface area is 771m 2 / g, pore volume is 0.52 cm 3 / g), 1% sesbania powder accounting for the total weight of alumina and molecular sieve, and 1% nitric acid aqueous solution by weight were mixed, rolled into a paste and then extruded. The extruded strips were dried at 120 °C for 4 hours and then calcined at 550 °C for 3 hours to obtain carrier strips. The conventional equal volume impregnation method was used to load WO with a catalyst weight percentage of 20 wt%. 3 and 5wt% NiO, the carrier strip was added into a pre-prepared impregnation solution of the same volume as the carrier water absorption, left to stand for 12 hours, dried at 120 °C in air atmosphere for 8 hours, and calcined at 450 °C for 4 hours to obtain catalyst C-1. The specific properties are shown in Table 2.
[0078] Example 2
[0079] (1) Preparation of composite molecular sieves
[0080] ① The concentration is 40 gAl 2 O 3 / L sodium aluminate working solution, take the SiO 2 28 wt% sodium silicate solution, diluted to a concentration of 150 gSiO 2 / L sodium silicate working solution. Take 200 mL of sodium aluminate working solution and place it in a gelling tank, then add 40 mL of sodium silicate working solution, control the reaction temperature at 25 °C, and introduce 50 v% CO 2 When the pH value reaches 10.5, stop the CO 2 , add 40 mL of sodium silicate working solution, and then pass the remaining CO 2 The gas was stable and after aging at 20 °C for 20 minutes, an amorphous silicon aluminum precursor was obtained. 2 :Al 2 O 3 :Na 2 O:H 2 O=1:0.005:0.04:60, IPA / SiO 2=0.15 total feed molar ratio, add isopropylamine to the amorphous silicon-aluminum precursor obtained above, stir at 20°C for 1 hour to obtain a mixed solution containing amorphous silicon-aluminum precursor and template agent; then, add a mixture consisting of sodium hydroxide, silica sol and water to it, stir evenly to obtain silicon-aluminum gel. Pour the above obtained gel into a stainless steel reactor and statically crystallize at 180°C for 18 hours. After the crystallization is completed, filter and wash to neutrality, and dry at 120°C to obtain the molecular sieve product NaZSM-23-2; weigh a certain amount of NaZSM-23-2 molecular sieve sample, place it in an ammonium nitrate solution with a concentration of 2 mol / L, and the liquid-to-solid ratio is 10. After continuous stirring in a water bath at 80~90°C for 1 hour, filter and wash. After repeating the above operation process twice, the sample was placed in an oven at 80-100 °C for 8 hours and calcined in an air atmosphere at 550 °C for 3 hours to obtain HZSM-23-2.
[0081] ② Preparation of HZSM-23@Al-SBA-15 composite molecular sieve
[0082] a) adding 15.0 g of tetraethyl orthosilicate to 50.0 g of HCl solution with a pH value of 2.0, stirring at 20° C. for 10 hours, and then standing for 24 hours to obtain a silicon source hydrolyzate;
[0083] b) 3.5 g P123 was dissolved in 250 mL 0.40 mol / L hydrochloric acid solution; 2.55 g aluminum isopropoxide, 17 g HZSM-23-2, and the silicon source hydrolyzate obtained in step ② a) were added successively, and stirred at room temperature for 4 hours; the resulting mixed solution was transferred to a hydrothermal reactor, crystallized at 100 ° C for 24 hours, filtered, washed to neutrality, dried at 100 ° C, and calcined in air at 550 ° C for 3 hours to obtain the molecular sieve product Z-2, and the relative crystallinity of its core molecular sieve was measured; after hydrothermal treatment with water vapor at 600 ° C for 2 hours, its hydrothermal stability was measured, and its XRD spectrum was consistent with Figure 1 and Figure 2 Similar, the specific properties are shown in Table 1.
[0084] (2) Catalyst preparation
[0085] Alumina (surface area 399 m 2 / g, pore volume 0.91 cm 3 / g), 40 wt% Z-2 molecular sieve, 6 wt% modified Y molecular sieve (SiO 2 / Al 2 O 3 The molar ratio is 40, the unit cell parameter is 2.466, and the specific surface area is 771m 2 / g, pore volume is 0.52 cm3 / g), 1% sesbania powder accounting for the total weight of alumina and molecular sieve, and 1% nitric acid aqueous solution by weight were mixed, rolled into a paste and then extruded. The extruded strips were dried at 120 °C for 4 hours and then calcined at 550 °C for 3 hours to obtain carrier strips. The conventional equal volume impregnation method was used to load WO with a catalyst weight percentage of 25 wt%. 3 and 5wt% NiO, the carrier strip was added into a pre-prepared impregnation solution of the same volume as the carrier water absorption, left to stand for 12 hours, dried at 120 °C in air atmosphere for 8 hours, and calcined at 450 °C for 4 hours to obtain catalyst C-2. The specific properties are shown in Table 2.
[0086] Example 3
[0087] (1) Preparation of composite molecular sieves
[0088] ① The concentration is 50 gAl 2 O 3 / L sodium aluminate working solution, take the SiO 2 28 wt% sodium silicate solution, and then diluted to a concentration of 100 gSiO 2 / L sodium silicate working solution. Take 200 mL of sodium aluminate working solution and place it in a gelling tank, then add 60 mL of sodium silicate working solution, control the reaction temperature at 30°C, and introduce 50v% CO 2 When the pH value reaches 10.0, stop the CO 2 , add 40 mL of sodium silicate working solution, and then pass the remaining CO 2 The gas was stable and after aging at 35°C for 15 minutes, an amorphous silicon-aluminum precursor was obtained. 2 :Al 2 O 3 :Na 2 O:H 2 O=1:0.01:0.04:30, IPA / SiO 2=0.4 total feed molar ratio, add isopropylamine to the amorphous silicon-alumina precursor obtained above, stir at 25 ºC for 0.5 hours to obtain a mixed solution containing amorphous silicon-alumina precursor and template agent; then, add a mixture of sodium hydroxide, silica sol and water to it, stir evenly to obtain silicon-alumina gel. Pour the gel obtained above into a stainless steel reactor and statically crystallize at 180 ℃ for 18 hours. After the crystallization is completed, filter and wash to neutrality, and dry at 120 ℃ to obtain the molecular sieve product NaZSM-23-3; weigh a certain amount of NaZSM-23-3 molecular sieve sample, place it in an ammonium nitrate solution with a concentration of 2 mol / L, and the liquid-to-solid ratio is 10. After continuous stirring in a water bath at 80~90 ℃ for 1 hour, filter and wash. After repeating the above operation process twice, the sample was placed in an oven at 80-100 °C for 8 hours and calcined in an air atmosphere at 550 °C for 3 hours to obtain HZSM-23-3.
[0089] ② Preparation of HZSM-23@Al-SBA-15 composite molecular sieve
[0090] a) Add 15.0 g of tetraethyl orthosilicate to 50.0 g of HCl solution with a pH value of 3.0, stir at 30°C for 8 hours, and let stand for 36 hours to obtain a silicon source hydrolyzate. ;
[0091] b) 3.93 g P123 was dissolved in 250 mL 0.50 mol / L hydrochloric acid solution; 3.41 g aluminum isopropoxide, 10 g HZSM-23-3, and the silicon source hydrolyzate obtained in step ② a) were added successively, and stirred at room temperature for 4 hours; the resulting mixed solution was transferred to a hydrothermal reactor, crystallized at 100 ° C for 24 hours, filtered, washed to neutrality, dried at 100 ° C, calcined at 550 ° C in air for 3 hours, and then calcined at 550 ° C in air for 3 hours to obtain a molecular sieve product Z-3, and the relative crystallinity of its core molecular sieve was measured; after hydrothermal treatment with water vapor at 600 ° C for 2 hours, its hydrothermal stability was measured, and its XRD spectrum was consistent with that of the product. Figure 1 and Figure 2 Similar, the specific properties are shown in Table 1.
[0092] (2) Catalyst preparation
[0093] Alumina (specific surface area 376 m 2 / g, pore volume 0.74 cm 3 / g), 15 wt% Z-3 molecular sieve, 4 wt% modified Y molecular sieve (SiO 2 / Al 2 O 3 The molar ratio is 25, the unit cell parameter is 2.468, and the specific surface area is 788m 2 / g, pore volume is 0.54 cm 3 / g), 1% sesbania powder accounting for the total weight of alumina and molecular sieve, and 1% nitric acid aqueous solution by weight were mixed, rolled into a paste and then extruded. The extruded strips were dried at 120 °C for 4 hours and then calcined at 550 °C for 3 hours to obtain carrier strips. The conventional equal volume impregnation method was used to load WO with a catalyst weight percentage of 20 wt%. 3 and 5wt% NiO, the carrier strip was added into a pre-prepared impregnation solution of the same volume as the carrier water absorption, left to stand for 12 hours, dried at 120 °C in air atmosphere for 8 hours, and calcined at 450 °C for 4 hours to obtain catalyst C-3. The specific properties are shown in Table 2.
[0094] Example 4
[0095] (1) Preparation of composite molecular sieves
[0096] ① The concentration is 20 gAl 2 O 3 / L sodium aluminate working solution, take the SiO 2 28 wt% sodium silicate solution, diluted to a concentration of 150 gSiO 2 / L sodium silicate working solution. Take 300 mL of sodium aluminate working solution and place it in a gelling tank, then add 20 mL of sodium silicate working solution, control the reaction temperature at 30 ºC, and introduce 50 v% CO 2 When the pH value reaches 11.0, stop the CO 2 , add 20 mL of sodium silicate working solution, and then pass the remaining CO 2 The gas was stable and after aging at 20 °C for 30 minutes, an amorphous silicon aluminum precursor was obtained. 2 :Al 2 O 3 :Na 2 O:H 2 O=1:0.01:0.04:45, IPA / SiO 2=0.3 total feed molar ratio, add isopropylamine to the amorphous silicon-aluminum precursor obtained above, stir at 15 ℃ for 1 hour, and obtain a mixed solution containing amorphous silicon-aluminum precursor and template agent; then, add a mixture of sodium hydroxide, silica sol and water to it, stir evenly, and obtain silicon-aluminum gel. The gel obtained above is poured into a stainless steel reactor and statically crystallized at 180 ℃ for 18 hours. After the crystallization is completed, it is filtered and washed to neutrality, and then dried at 120 ℃ to obtain the molecular sieve product NaZSM-23-4; weigh a certain amount of NaZSM-23-4 molecular sieve sample, place it in an ammonium nitrate solution with a concentration of 2 mol / L, the liquid-to-solid ratio is 10, and continue to stir in a water bath at 80~90 ℃ for 1 hour, filter and wash. After repeating the above operation process twice, the sample is placed in an oven at 80~100 ℃ for 8 hours and calcined at 550 ℃ in air atmosphere for 3 hours to obtain HZSM-23-4.
[0097] ② Preparation of HZSM-23@Al-SBA-15 composite molecular sieve
[0098] a) adding 15.0 g of tetraethyl orthosilicate to 80.0 g of HCl solution with a pH value of 1.0, stirring at 35° C. for 6 hours, and then standing for 24 hours to obtain a silicon source hydrolyzate;
[0099] b) 3.0 g P123 was dissolved in 200 mL 0.50 mol / L hydrochloric acid solution; 1.75 g aluminum isopropoxide, 10 g HZSM-23-4, and the silicon source hydrolyzate obtained in step ② a) were added successively, and stirred at room temperature for 4 hours; the resulting mixed solution was transferred to a hydrothermal reactor, crystallized at 100 ° C for 24 hours, filtered, washed to neutrality, dried at 100 ° C, and calcined in air at 550 ° C for 3 hours to obtain the molecular sieve product Z-4, and the relative crystallinity of its core molecular sieve was measured; after hydrothermal treatment with water vapor at 600 ° C for 2 hours, its hydrothermal stability was measured, and its XRD spectrum was consistent with that of the product. Figure 1 and Figure 2 Similar, the specific properties are shown in Table 1.
[0100] (2) Catalyst preparation
[0101] Alumina (surface area 376 m 2 / g, pore volume 0.74 cm 3 / g), 15 wt% Z-4 molecular sieve, 3 wt% modified Y molecular sieve (SiO 2 / Al 2 O 3 The molar ratio is 25, the unit cell parameter is 2.468, and the specific surface area is 788m 2 / g, pore volume is 0.54 cm3 / g), 1% sesbania powder accounting for the total weight of alumina and molecular sieve, and 1% nitric acid aqueous solution by weight were mixed, rolled into a paste and then extruded. The extruded strips were dried at 120 °C for 4 hours and then calcined at 550 °C for 3 hours to obtain carrier strips. The conventional equal volume impregnation method was used to load WO with a catalyst weight percentage of 18 wt%. 3 and 4wt% NiO, the carrier strip was added into a pre-prepared impregnation solution of the same volume as the carrier water absorption, left to stand for 12 hours, dried at 120 °C in air atmosphere for 8 hours, and calcined at 450 °C for 4 hours to obtain catalyst C-4. The specific properties are shown in Table 2.
[0102] Comparative Example 1 (refer to CN106513035A)
[0103] (1) Preparation of composite molecular sieves
[0104] 1.38 gAl 2 SO 4 1.36 g NaOH was dissolved in 12.8 g deionized water, 7.28 g pyrrolidine was added and stirred thoroughly, and 48.29 g silica sol (40 wt% SiO 2 ), stirring until gel is formed, the molar ratio of SiO 2 :0.0125Al 2 O 3 :0.05Na 2 O:0.32Pyrrolidine:10H 2 O; transfer the formed gel to a high-pressure reactor, heat and stir, crystallize at 180 °C for 72 hours, wash, filter, and dry at 120 °C to obtain the molecular sieve product DNa-ZSM-23-1; weigh a certain amount of DNa-ZSM-23-1 molecular sieve sample, place it in a 2 mol / L ammonium nitrate solution with a liquid-to-solid ratio of 10, stir it in a water bath at 80~90 °C for 1 hour, filter and wash. After repeating the above operation twice, place the sample in an oven at 80~100 °C for 8 hours and calcine it in an air atmosphere at 550 °C for 3 hours to obtain DHZSM-23-1.
[0105] Weigh 6 g of P123 and dissolve it in 144 g of deionized water. Then add 6.24 g of silica sol (40 wt% SiO 2), 0.31 g aluminum sulfate, 10 g DHZSM-23-1 molecular sieve powder, mixed evenly, and finally added a certain amount of HCl to adjust the solution pH to 2-4. After stirring for 2 hours, the obtained mixed slurry was transferred to a hydrothermal reactor and crystallized at 100 °C for 24 hours. The reaction product was filtered and washed to neutrality, dried at 100 °C, and calcined in air at 550 °C for 3 hours to obtain the molecular sieve product DZ-1. Its properties are shown in Table 1.
[0106] (2) Catalyst preparation
[0107] Alumina (surface area 387 m 2 / g, pore volume 0.82 cm 3 / g), 20 wt% DZ-1 molecular sieve, 5 wt% modified Y molecular sieve (SiO 2 / Al 2 O 3 The molar ratio is 25, the unit cell parameter is 2.468, and the specific surface area is 788m 2 / g, pore volume is 0.54 cm 3 / g), 1% sesbania powder accounting for the total weight of alumina and molecular sieve, and 1% nitric acid aqueous solution by weight were mixed, rolled into a paste and then extruded. The extruded strips were dried at 120 °C for 4 hours and then calcined at 550 °C for 3 hours to obtain carrier strips. The conventional equal volume impregnation method was used to load WO with a catalyst weight percentage of 20 wt%. 3 and 5wt% NiO, the carrier strip was added into a pre-prepared impregnation solution of the same volume as the water absorption of the carrier, left to stand for 12 hours, dried at 120°C in air atmosphere for 8 hours, and calcined at 450°C for 4 hours to obtain catalyst DC-1. The specific properties are shown in Table 2.
[0108] Comparative Example 2
[0109] (1) Preparation of composite molecular sieves
[0110] Water glass, aluminum sulfate, isopropylamine (IPA), sodium hydroxide and water are mixed to prepare a total molar ratio of SiO in the silicon source. 2 :Al in aluminum source 2 O 3 :NaOH:IPA:H 2O=1:0.01:0.08:1.0:50, heated at 180 °C for 72 hours, washed, filtered, and dried at 120 °C to obtain the molecular sieve product DNa-ZSM-23-2; weigh a certain amount of DNa-ZSM-23-2 molecular sieve sample, place it in a 2 mol / L ammonium nitrate solution with a liquid-to-solid ratio of 10, and continue stirring in a water bath at 80~90 °C for 1 hour, filter and wash. After repeating the above operation twice, the sample was placed in an oven at 80~100 °C for 8 hours and calcined at 550 °C in air atmosphere for 3 hours to obtain DHZSM-23-3.
[0111] 15.0 g of tetraethyl orthosilicate was added to 50.0 g of HCl solution with a pH of 2.0, and the mixture was stirred at room temperature for 4 hours and allowed to stand for 36 hours to obtain a silicon source hydrolyzate.
[0112] 3.0 g P123 was dissolved in 250 mL 0.30 mol / L hydrochloric acid solution; 2.55 g aluminum isopropoxide, 10 g DHZSM-23-3, and the silicon source hydrolyzate obtained in step (2) ① were added successively and stirred at room temperature for 4 hours; the resulting mixed solution was transferred to a hydrothermal reactor, crystallized at 100 ° C for 24 hours, filtered, washed to neutrality, dried at 100 ° C, and calcined in air at 550 ° C for 3 hours to obtain the molecular sieve product DZ-2. The specific properties are shown in Table 1.
[0113] (2) Catalyst preparation
[0114] Alumina (surface area 387 m 2 / g, pore volume 0.82 cm 3 / g), 20 wt% DZ-2 molecular sieve, 5 wt% modified Y molecular sieve (SiO 2 / Al 2 O 3 The molar ratio is 25, the unit cell parameter is 2.468, and the specific surface area is 788m 2 / g, pore volume is 0.54 cm 3 / g), 1% sesbania powder accounting for the total weight of alumina and molecular sieve, and 1% nitric acid aqueous solution by weight were mixed, rolled into a paste and then extruded. The extruded strips were dried at 120 °C for 4 hours and then calcined at 550 °C for 3 hours to obtain carrier strips. The conventional equal volume impregnation method was used to load WO with a catalyst weight percentage of 20 wt%. 3 and 5wt% NiO, the carrier strips were added with a pre-prepared impregnation solution of the same volume as the carrier water absorption, left to stand for 12 hours, dried at 120°C in air atmosphere for 8 hours, and calcined at 450°C for 4 hours to obtain catalyst DC-2. The specific properties are shown in Table 2.
[0115] Table 1
[0116]
[0117] Table 2
[0118]
[0119] The activity of the above-mentioned catalysts C-1, C-2, C-3, C-4 of the present invention and the comparative catalysts DC-1 and DC-2 were evaluated in a fixed bed reactor. The specific reaction conditions were: reaction temperature 330 °C, pressure 10.0 MPa, volume space velocity 1.0 h -1 , hydrogen-to-oil ratio is 1000, the properties of the feed oil are shown in Table 3, and the reaction results are shown in Table 4.
[0120] It can be seen from the reaction result data table in Table 4 that under the same reaction conditions, the diesel fraction yield and the pour point of the catalyst of the present invention are better than those of the catalyst prepared by the prior art.
[0121] Table 3 Raw oil properties
[0122]
[0123] Table 4 Catalyst performance evaluation results
[0124]
Claims
1. A hydrogenation catalyst, characterized in that: Based on the weight of the final catalyst, it includes the following components: a) HZSM-23@Al-SBA-15 composite molecular sieve, content is 10~50wt%; b) Modified Y molecular sieve, content is 2~8wt%; c) Alumina, content of 25~65wt%; d) Group VIB and / or Group VIII active metals, wherein the content of Group VIB metals as oxides is 10-30 wt%, and the content of Group VIII metals as oxides is 3-10 wt%; The HZSM-23@Al-SBA-15 composite molecular sieve has HZSM-23 molecular sieve as the core and Al-SBA-15 molecular sieve as the shell, wherein the crystallinity of the core molecular sieve is 97-110%. The total acid content of the HZSM-23@Al-SBA-15 composite molecular sieve is 0.07-0.35 mmol / g, and the weak acid content is 60-95%.
2. The catalyst according to claim 1, characterized in that: Based on the weight of the final catalyst, it includes the following components: a) HZSM-23@Al-SBA-15 composite molecular sieve, content of 15~45wt%; b) Modified Y molecular sieve, content is 3~6wt%; c) Alumina, content is 30~60wt%.
3. The catalyst according to claim 1 or 2, characterized in that: The core molecular sieve has a crystallinity of 97-108%.
4. The catalyst according to claim 1, characterized in that: After the composite molecular sieve is hydrothermally treated with 600° C. steam for 2 hours, the crystallinity of the core molecular sieve is 95-108%.
5. The catalyst according to claim 4, characterized in that: After the composite molecular sieve is hydrothermally treated with 600° C. steam for 2 hours, the crystallinity of the core molecular sieve is 96-105%.
6. The catalyst according to claim 1, characterized in that: The total acid content of the catalyst is 0.100-0.285 mmol / g, and the weak acid content is 50-85%.
7. The catalyst according to claim 6, characterized in that: The total acid content of the catalyst is 0.110-0.280 mmol / g, and the weak acid content is 53-82%.
8. The catalyst according to claim 1, characterized in that: The mesopore volume of the catalyst accounts for 15-60% of the total pore volume.
9. The catalyst according to claim 8, characterized in that: The mesopore volume of the catalyst accounts for 18-55% of the total pore volume.
10. The catalyst according to claim 1, characterized in that: The specific surface area of the catalyst is 250-400 m 2 / g, pore volume is 0.50~0.85 cm 3 / g.
11. The catalyst according to claim 10, characterized in that: The specific surface area of the catalyst is 260-385 m 2 / g, pore volume is 0.53~0.80 cm 3 / g.
12. The catalyst according to claim 1, characterized in that: In the Al-SBA-15 molecular sieve, the mass content of Al in terms of alumina is 2.45-10.05% based on the weight of the Al-SBA-15 molecular sieve; the core-shell mass ratio in the composite molecular sieve is 1:1-1:
9.
13. The catalyst according to claim 12, characterized in that: The mass content of Al in the Al-SBA-15 molecular sieve as alumina is 2.83-8.50% based on the weight of the Al-SBA-15 molecular sieve; the core-shell mass ratio in the composite molecular sieve is 1:2-1:
4.
14. The method for preparing the catalyst according to any one of claims 1 to 13, characterized in that: The method comprises the following steps: (1) Preparation of HZSM-23@Al-SBA-15 composite molecular sieve; (2) mixing the HZSM-23@Al-SBA-15 prepared in step (1), the modified Y molecular sieve, alumina and a binder, forming, drying and calcining to obtain a carrier; (3) Introducing active metal components into the carrier obtained in step (2), and obtaining the final catalyst after drying and calcining.
15. The method according to claim 14, characterized in that: The HZSM-23@Al-SBA-15 composite molecular sieve in step (1) has HZSM-23 molecular sieve as the core and Al-SBA-15 molecular sieve as the shell, wherein the crystallinity of the core molecular sieve is 97-110%, and after the composite molecular sieve is hydrothermally treated with water vapor at 600° C. for 2 hours, the crystallinity of the core molecular sieve is 95-108%.
16. The method according to claim 15, characterized in that: The crystallinity of the core molecular sieve is 97-108%. After the composite molecular sieve is hydrothermally treated with 600° C. steam for 2 hours, the crystallinity of the core molecular sieve is 96-105%.
17. The method according to claim 14, characterized in that: The total acid content of the HZSM-23@Al-SBA-15 composite molecular sieve in step (1) is 0.09-0.32 mmol / g; and the weak acid content is 65-92%.
18. The method according to claim 14, characterized in that: The micropore volume of the HZSM-23@Al-SBA-15 composite molecular sieve in step (1) accounts for 15-90% of the total pore volume, and the specific surface area is 310-470 m 2 / g, pore volume is 0.31~0.68 cm 3 / g.
19. The method according to claim 18, characterized in that: The micropore volume of the HZSM-23@Al-SBA-15 composite molecular sieve in step (1) accounts for 20-85% of the total pore volume; the specific surface area of the composite molecular sieve is 330-460 m 2 / g, pore volume is 0.32~0.65 cm 3 / g.
20. The method according to claim 14, characterized in that: The modified Y molecular sieve in step (2) has a SiO2 / Al2O3 molar ratio of 25-90, a unit cell parameter of 2.460-2.470, and a specific surface area of 550-850 m 2 / g, pore volume is 0.35~0.53 cm 3 / g.
21. The method according to claim 14, characterized in that: The properties of the alumina in step (2) are: specific surface area 375~400 m 2 / g, pore volume 0.60~0.95 cm 3 / g.
22. The method according to claim 14, characterized in that: In step (2), the carrier is dried and calcined by conventional methods, specifically as follows: the drying temperature is 80-120°C and the time is 2-12 hours; the calcination temperature is 530-570°C and the time is 3-6 hours.
23. The method according to claim 14, characterized in that: The active metal component in step (3) is one or a combination of two of Mo, W, Ni, Fe, and Co.
24. The method according to claim 23, characterized in that: The active metal component in step (3) is a combination of W-Ni and Mo-Ni.
25. The method according to claim 14, characterized in that: The active metal is loaded by impregnation in step (3). After impregnation, the carrier is dried at 80-120°C for 4-7 hours and then calcined at 400-700°C for 3-12 hours to obtain the final catalyst.
26. Use of the catalyst according to any one of claims 1 to 13 in diesel hydrogenation reaction, characterized in that: The total mass content of paraffins and cycloparaffins in the diesel is 61-85%, the mass content of paraffins is 32-50%, and the mass content of cycloparaffins is 20-40%.
27. The use according to claim 26, characterized in that: The total mass content of paraffins and cycloalkanes in the diesel is 62-83%, the mass content of paraffins is 34-47%, and the mass content of cycloalkanes is 22-38%.
28. The use according to claim 26, characterized in that: The diesel density is 0.870-0.930 g / cm 3 , the distillation range is 150~390℃.
29. The use according to claim 28, characterized in that: The diesel density is 0.880-0.925 g / cm 3 .
30. The use according to claim 26, characterized in that: The reaction conditions are as follows: reaction temperature 320~400℃, total reaction pressure 4.0~12.0 MPa, liquid hourly volume space velocity 0.4~2.0 h -1 , hydrogen-oil volume ratio 400:1~1200:1.
Citation Information
Patent Citations
Preparation method of n-alkane hydroisomerization catalyst
CN108816279A
Preparation method of high-activity isomerization pour point depressing catalyst
CN111659462A
Preparation method for mesoporous-microporous composite hydroisomerization dewaxing catalyst
CN106513035A
Diesel oil hydro-upgrading catalyst as well as preparation method and application thereof
CN114433209A
Distillate oil hydrogenation catalyst and its preparation method
CN1766053A